IMPLEMENTASI TEKNIK TWO STAY TWO STRAY DALAM PEMBELAJARAN BAHASA INDONESIA SEBAGAI UPAYA MENINGKATKAN HASIL BELAJAR - SUPRI ATMAJA (Pusat Pengembangan Pendidikan dan Penelitian indonesia (P4I), 2022)
This study aims to improve student learning outcomes by applying the Two Stay Two Stray technique in learning Indonesian. This research is a type of classroom action research conducted in class IX A of SMP Negeri 1 Pandak. Data was collected by means of observation sheets, tests, documentation, questionnaires, and interviews. Data on learning outcomes and student participation in learning were analyzed using quantitative descriptive techniques, while data on the implementation of learning were analyzed using qualitative descriptive techniques. The results of the analysis show that student learning outcomes have increased. This can be seen from the increase in student learning outcomes each cycle. The learning outcomes before the classical study completeness study were only 32%, in the first cycle it increased to 60%, and in the second cycle it increased again to 80% with an average increase of 29%. The increase in learning outcomes does not only occur in the cognitive aspect, but also in the affective and psychomotor aspects. In the affective aspect, it is shown by the development of students' cooperative skills, and in the psychomotor aspect, it is indicated by the ability of students to compose presentation materials. ABSTRAKPenelitian ini bertujuan untuk meningkatkan hasil belajar siswa dengan menerapkan teknik Two Stay Two Stray pada pembelajaran Bahasa Indonesia. Penelitian ini merupakan jenis penelitian tindakan kelas yang dilakukan di kelas IX A SMP Negeri 1 Pandak. Pengumpulan data dilakukan dengan lembar observasi, tes, dokumentasi, angket, dan wawancara. Data hasil belajar dan partisipasi siswa dalam pembelajaran dianalisis dengan menggunakan teknik deskriptif kuantitatif, sedangkan data pelaksanaan pembelajaran dianalisis menggunakan teknik deskriptif kualitatif. Hasil analisis menunjukkan bahwa hasil belajar siswa mengalami peningkatan. Hal ini dapat dilihat dari peningkatan hasil belajar siswa setiap siklusnya. Hasil belajar sebelum penelitian ketuntasan belajar klasikal hanya 32%, pada siklus I meningkat menjadi 60%, dan pada siklus II meningkat lagi menjadi 80% dengan rata-rata peningkatan sebesar 29%. Peningkatan hasil belajar tidak hanya terjadi pada aspek kognitif, tetapi juga pada aspek afektif dan psikomotor. Pada aspek afektif ditunjukkan oleh semakin berkembangnya keterampilan kooperatif siswa, dan pada aspek psikomotor ditunjukkan oleh kemampuan siswa menyusun bahan presentasi.